Through the bamboos, Trinidad - (:unkn) unknown (Wilson Ltd., Trinidad, 2010)
A view of bamboos gently arching over a road somewhere in Trinidad. No.5378
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bamboo; Rural roads